Letter : Spanish Relief Fund - Beer, Cecil J.
029-0147-001 VICECONSULADO DE ESPANA. Tel. 2222. Newport, Mon. My ref: No. 35. Your ref: HVT/EK/979. Secretary's Dept. May 29th, 1937. The Trades Union Congress General Council, S. W. 1. Dear Sirs, SPANISH RELIEF FUND.- I thank you for your letter of 28th instant, which crossed mine of that date, and note with interest all you write. I trust you will succeed in seeing a representative of the Spanish Women's Committee on Monday, and might mention that whereas the address of this Committee was given to me by the Consulate at Cardiff as being 22, Taunton Avenue, S.W. 20, I notice from their letter-heading it is 16, Lloyd's Square. W.C.1., telephone - Terminus 4493. Your further news in due course would be much appreciated and in the meantime I remain, dear Sirs, Yours faithfully, Cecil J Beer Viceconsul for Spain at Newport, Mon. VICE CONSULADO DE ESPANA EN NEWPORT 292/946/29/147